(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
This article discusses today’s current issues – language and culture, their mutual relations, the linguistic and cultural aspects of the repetitions in the English translation of the rare work “Alpomish”, which embodies the national customs and traditions of the Uzbek people. The ability of the translator, who is a bridge between two unrelated languages, as well as suggestions and recommendations on translation difficulties and their elimination, are given. By the word dance, it is meant that the participation of words, phrases, and sentences that come as a means of repeated expression decorates the epic in terms of content and form.